Types and Reasons of Women Crimes (The applicable study in correctional institution–Women Section in Sulaimania). - حمة ويس نصر الله, واحدة (Al-Adab Journal, 2018)
The study focuses on women crimes which have been recently increased as a result of political, economic and social changes. The main aim of the study is to reveal and know the types and reasons of women crimes. The study is descriptive one, conducted with content analysis that consists of an introduction and the theoretical framework of the study. The researcher tried to explain the importance of the study, study problems, study goals, and conducting approaches and methods of study. The practical framework of the study is the second part. It includes the samples of the research that consist of (34) criminal women from correctional institution-women section in Sulaimania, which have been chosen by comprehensive-survey method. The study concluded that:1-Most criminals were married, and their marriage was obligatory marriage.2- Murder crimes were in the top of the other crimes.3- Drug use and drugs trafficking were the second most committed crimes .4- Moral crimes came in the third level .5-Most of prisoners were exposed to abuse and violence in front of their husbands., and some of them considered that was main reason pushed them for committing crime. Most murders were husband murders committed with lovers.6-The gun was the most mean used in the murders.Lastly, the researcher offered some precious and valuable suggestions that would be beneficial to decrease women crimes.